Dengue e o Aedes aegypti na população indígena dos Tremembé da aldeia Tapera no Ceará: prevalência, conhecimentos e práticas - Sacramento, Rafael Henrique Machado (2017)
INTRODUCTION: Dengue remains an important public health problem. The indigenous peoples of the Northeast were the first to be contacted in the Portuguese colonial invasion, and have since suffered the social and health consequences of this historical moment. Despite recent efforts to address this vulnerable population, there are few records of dengue among Brazilian Indians. PURPOSE: to determine the risk of dengue transmission and the seroprevalence of the disease among TREMEMBÉ natives (Tapera village in the city of Itarema, Ceará), as well as aspects related to infestation by mosquitoes of the genus Aedes. MATERIAL AND METHODS: a cross-sectional study, a seroepidemiological survey (part I) and a prospective environmental study of monthly traps for mosquito eggs collection (part II) were carried out. The sub-study I involved 350 Tremembé Indians living in the village of Tapera, municipality of Itarema, Ceará. The association between the results of serological screening (IgG) and the epidemiological variables investigated were analyzed using contingency tables, using the Prevalence Ratio and tested by the Fisher's exact test, with a 95% confidence interval and with defined statistical significance As p <0.05. For the sub-study II, 42 houses were randomly randomized. In each residence a trap (ovitrampa) was installed inside and outside the house, composing the 84 traps monitored. These traps were inspected for 12 consecutive months. The reeds were removed weekly, put to dry and then the eggs were counted. The data were entered and analyzed using Epiinfo software in version 3.5.1. The project was approved by all the ethical instances required for projects involving special populations. RESULTS: The Tremembé da Tapera are mostly in the economically active age (65.1%) and 62% consider themselves illiterate or with low schooling. More than half (62.5%) have a family income below a salary and only 35.5% of them move more frequently to the city. Fever was the most cited symptom among the natives (82.7%), followed by pain in the muscles (66.2%), eyes (63.4%), joints (57.6%) and vomiting %). The most cited measure of control was to eliminate standing water (76.4%) and to place sand in the plant pots (76.4%). Most houses are masonry (95.7%), garbage is burned by 44.4% of families and 77% has regular water supply. Seroprevalence was 22.1% (62/280), of which 39 were women (63%) and 23 were men (37%). Positivity increased with age, being 4.2%; 26.8% and 42.3% for the groups of <15 years, 15 to 59 and> 59 years; Respectively (p <0.001). He was also associated with the belief that he had dengue, a higher frequency of dislocation to the city and presence of basic diseases. Eggs were collected in all months of the year and in all households. The highest collection occurred in March (3,145 eggs) and the lowest in September (379 eggs). More eggs were collected in traps located outside the home (57%). In six houses there were trapping eggs in 11 of the 12 months of monitoring. CONCLUSION: the prevalence of dengue among the Tremembé was high compared to other rural regions, even though they have a reasonable knowledge about symptoms and prevention measures. The mosquito infestation of the genus Aedes was very high in the village, with persistence throughout the year.